Práticas de ensino de matemática: regimes e jogos de verdade na formação do professor nos anos iniciais (1960-2000) - Pozzobon, Marta Cristina Cezar (Universidade do Vale do Rio dos Sinos, 2012)
From approximations to both Foucauldian studies and investigations in the areas of education and mathematical education, this thesis problematizes the education provided by a Teaching Course from 1960 to 2000 in a countryside high school in Rio Grande do Sul to teachers who teach mathematics to the early grades. The questions that have guided this research are the following: How did mathematical knowledge constitute the mathematics teaching practices of the high school Teaching Course analyzed? Which mathematics teaching practices operated on the education of early grade teachers in the period analyzed? In order to address these questions, the analytical tools of ‘discursive education practices’, ‘regimes of truth’ and ‘games of truth’ were considered along the analysis of the material, which consisted of the following: a training record book, eight interviews with teachers that taught the Course, four questionnaires applied to training supervisors, a planning notebook, a Mathematics Experimental Program, two planning booklets and two training proposals. Two movements resulted from the analysis, and they were named as regimes and games of truth. The first one is related to regimes of truth constituted in the production of the development of reasoning and behavior, from the alliance between psychology and pedagogy in the late nineteenth century and early twentieth century by investing in practices directed to reasoning development, production of intelligent subjects, concept learning, use of concrete material, and logical reasoning. In the second movement, the games of truth and a politics of truth emphasize mathematics teaching practices directed to discourses of pedagogy centered on the child, in the critical pedagogy, in which the emphasis has been put on teaching from the child’s interest, the generating topic, the globalization and the student’s reality. Such games of truth have produced effects on teacher education by producing other kind of mathematics, one that assumes the function of political struggle, of enlightenment of consciences of students and teachers. With these practices, other ways of regarding and talking about mathematics, teachers and students have been produced. The analysis has led to the argument that the mathematics teaching practices of early grades both constitute and are constituted by games of truth, involving the conceptions of scientific knowledge, mathematics knowledge, teaching knowledge and subject in different times, and such conceptions are articulated by the reason of a governmentalized State.
Keywords: Práticas de ensino de matemática; Jogos de verdade; Anos iniciais; Formação de professores; Mathematics teaching practices; Games of truth; Early grades; Teacher education; ACCNPQ::Ciências Humanas::Educação